(untitled) (Comprehensive Journal of Science, 2025)
This study investigated the potential interaction and combined toxicity of the heavy metal Cadmium (Cd) with two common pesticides—the organophosphate insecticide Salute (Chlorpyrifos) and the herbicide Round-up (Glyphosate)—on the growth and reproduction of the earthworm species, Eisenia fetida, under laboratory conditions. Eight adult to pre-adult worms were exposed for eight weeks to single treatments of Cd, Salute, or Round-up, as well as their metal-pesticide mixtures, using concentrations based on field use and typical unpolluted soil levels for Cd (5 mg/Kg). Significant differences in worm body weight were reported after eight weeks among the different treatments compared to the control (F=6.19, P<0.05). The lowest body weight was recorded in the Cd-Salute mixture (7.24 ± 1.02 g), indicating a synergistic interaction and a moderate to low effect on body weight. Conversely, the highest body weight was observed in the Cd-Round-up mixture (9.83 ± 2.69 g), suggesting a relative antagonistic effect when combined, though the difference was not statistically significant. For reproduction, measured by juvenile numbers, the Cd-Salute mixture did not show significant differences compared to the control. However, the Cd-Round-up mixture revealed a significant difference (F=29.809, P<0.05), with the Round-up treatment alone having the least mean juvenile number (133.3 ± 89.04), followed by the Cd-Round-up mixture (169.6 ± 51.08). This result indicated that Round-up seemed to have a greater negative impact on juvenile production, and the mixture with Cd reflected an additive effect. Overall, the results confirm that the mixed pollutants can lead to impacts on chronic responses like growth and reproduction. The combination of the herbicide Round-up and Cadmium had an adverse effect on juvenile number, while the insecticide Salute and its metal combination did not show an obvious negative effect on juveniles.